A ONE NON-TRADITIONAL DICTIONARY OF INITIAL ABBREVIATIONS FROM THE FIELD OF ICT - LAVRINČÍK, Jan; NEUMANN, Karel (Trends in education, 2008)
The study presents the ways of record, sort and interpretation of new initial abbreviations from the field of ICT. The origins of words are explained. Apposite definition and translations are suggested. At the end, it argues about the present use of them.
Keywords: abbreviations definition; initial abbreviations; dictionary of ICT abbrevations.